2022
DOI: 10.1101/2022.03.31.22273221
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Immunogenicity and reactogenicity of SARS-CoV-2 vaccines in people living with HIV: a nationwide prospective cohort study in the Netherlands

Abstract: Background Vaccines can be less immunogenic in people living with HIV (PLWH), but for SARS-CoV-2 vaccinations this is unknown. Methods and Findings A prospective cohort study to examine the immunogenicity of BNT162b2, mRNA-1273, ChAdOx1-S and Ad26.COV2.S vaccines in adult PLWH, without prior COVID-19, compared to HIV-negative controls. The primary endpoint was the anti-spike SARS-CoV-2 IgG response after mRNA vaccination. Secondary endpoints included the serological response after vector vaccination, anti-S… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 35 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…As we hypothesized that this also holds true for SARS-CoV-2 vaccines, we previously investigated the immunogenicity of SARS-CoV-2 vaccinations in PLWH with the vaccines currently approved in the Netherlands. Whereas smaller studies showed variable antibody responses after SARS-CoV-2 vaccination in PLWH compared to HIV-negative controls[39], our study in 1154 PLWH clearly demonstrated a diminished antibody response[10]. In total, 165 (14.3%) of the participants were hyporesponders (≤300 spike (S)-specific binding antibody units [BAU]/mL by chemiluminescence immunoassay [DiaSorin Liaison]) and in 33 of them the antibody level remained below the cut-off level of test positivity (33.8 BAU/mL).…”
Section: Introductionmentioning
confidence: 62%
“…As we hypothesized that this also holds true for SARS-CoV-2 vaccines, we previously investigated the immunogenicity of SARS-CoV-2 vaccinations in PLWH with the vaccines currently approved in the Netherlands. Whereas smaller studies showed variable antibody responses after SARS-CoV-2 vaccination in PLWH compared to HIV-negative controls[39], our study in 1154 PLWH clearly demonstrated a diminished antibody response[10]. In total, 165 (14.3%) of the participants were hyporesponders (≤300 spike (S)-specific binding antibody units [BAU]/mL by chemiluminescence immunoassay [DiaSorin Liaison]) and in 33 of them the antibody level remained below the cut-off level of test positivity (33.8 BAU/mL).…”
Section: Introductionmentioning
confidence: 62%